Penerapan Kurikulum Pendidikan Agama Kristen Sekolah Minggu dengan Menggunakan Teori Maria Harris - Iman Setia Telaumbanua; Lusia Rahajeng; Hasahatan Hutahaean (Jurnal Shanan, 2022)
The curriculum is the center or center of educational activities that greatly affect the implementation of the teaching and learning process. Due to the large influence of the curriculum on the implementation of teaching and learning activities, it is necessary to develop a curriculum that is in accordance with the needs of teaching and learning activities. One of the Christian education experts who contributed to the curriculum in the church is Maria Harris. Curriculum development begins with goal setting and is implemented in the Christian community. Maria Harris curriculum development offers new insights into the design of the Christian education curriculum model, which in this case can be recognized by its design and "educational" aesthetic characteristics. The purpose of this study was to design the Sunday School PAK curriculum using the Maria Harris theory. The research method used in this study is a qualitative research method that refers to library research, where researchers will use various literatures such as books or articles and other sources that are accurate and related to the application of the Maria Harris curriculum to the preparation of Christian Religious Education. Sunday school. The results of this study indicate that the application of the Maria Harris curriculum can help the church to be able to fulfill its duties and vocations through the stages in preparing the Sunday school curriculum.